Analysis of Factors Influencing Financial Statement Fraud With Company Size As An Intervening Variable In The Stock Exchange of Thailand - Lia Nurfarida; Haifa Haifa; Mainatul Ilmi (LPPM Institut Teknologi dan Sains Mandala, 2023)
This study aimed to analyze the factors that influence financial statement fraud with company size as an intervening variable. The data that used were financial statements (annual report) during 2015-2019. The sample method was purposive sampling. The whole samples consisted of 13 property and construction company that listed in Stock Exchange of Thailand. Data analysis technique that used was path analysis. The result showed that financial target and quality of external auditor have significant effect to company size, while ineffective monitoring, change of company director and the number of photos CEO have no significant effect. Quality of external auditor, change of company director and company size have significant effect to financial statement fraud, while financial target, ineffective monitoring and the number of photos CEO have no significant effect. Company size can be intervening variable between financial target, quality of external auditor and the number of photos CEO in financial statements to financial statement fraud.